Functional outcomes of tibiotalocalcaneal arthrodesis using a hindfoot arthrodesis nail in treating Charcot's arthropathy deformity - Bajuri, Mohd Yazid; Manas, Ammar Muizuddin; Zamri, Kamarul Syarazi (Frontiers in Surgery, 2023)
ABSTRACT Background: Tibiotalocalcaneal arthrodesis (TTCA) or hindfoot fusion is a salvage surgical option used to treat symptomatic or severe deformity as a result of Charcot’s arthropathy. It is an internal fixation which utilizes nails to stabilize the hindfoot after surgical correction of the deformity. This study intends to measure the change in functional outcomes of patients with Charcot’s arthropathy using this technique and the time taken to achieve fusion. Method: This study presents a series of 40 cases of Charcot’s arthropathy where hindfoot fusion was done using an hindfoot arthrodesis nail. A retrospective analysis was done where these patients’ functional scores had been evaluated pre-operatively and post-operatively (serially) with Short Form Health Survey 36 (SF-36), American Orthopedic Foot and Ankle Society (AOFAS), Foot and Ankle Outcome Score (FAOS) and Foot Function Index (FFI). Along with its complication, the length of time required for fusion is also reported. Results: This study consists of forty patients where 27 are female and 13 are male. The mean age was 60.5 (52 to 68) years with a mean follow-up of 64 months (24 to 108). The average time taken for fusion was 5.1 months. All patients showed improvement in functional scoring (SF 36, AOFAS, FFI and FAOS) postoperatively. We establish that the improvements were gradual over 2 years. About 37.5% of patients had minor complication and 2.5% had major complication. Conclusion: Hindfoot fusion using Hindfoot Arthrodesis Nail results in improved functional outcome with an acceptable fusion time and acceptable complication rate.